Integrated management of cowpea insect pests using elite cultivars, date of planting and minimum insecticide application - Asante, S.; Tamo, Manuele; Jackai, L.E.N. (African Journals Online, 2001)
Trials were conducted in Kano, northern Nigeria, during 1996 and 1997 cropping seasons to determine the influence of date of planting and two well-timed insecticides sprays on the incidence of major insect pests namely, the legume pod-borer, Maruca vitrata Fab., legume flower thrips, Megalurothrips sjostedti Trybom, complex of pod-sucking bugs and cowpea aphid, Aphis craccivora Koch and their effect on grain yield of elite cowpea (Vigna unguiculata L. Walp) cultivars from International Institute of Tropical Agriculture (IITA) breeding programme. Six cultivars were planted at 4 different dates between 13 June and 12 August 1996 whilst 12 cultivars were planted at 5 different dates between 5 June and 12 August 1997 with and without insecticide protection. Aphid infestation occurred only on cowpea planted between the first week of June and mid-July with the highest incidence recorded on crop planted in the last week of June. Cowpea planted in June flowered and podded between early to mid-August when post-flowering pests (M. vitrata, M. sjostedti and Clarigralla tomentosicollis) densities were relatively low and produced significantly higher grain yields without insecticide protection compared to other planting dates. The flowering and pod formation stages of late planted (July and August) crops coincided with the peak population densities of the three major post-flowering pests resulting in a considerable reduction of grain yield. Overall, IT90K-277-2, IT93K-734, IT93K-452-1 and IT93K-513-2 performed best whereas IT86D-719, IAR-48 and Dan Ila gave the poorest performance when unsprayed. Two insecticide sprays of Cypermethrin + dimethoate (Sherpa plus ®) (30 + 250g a.i. ha-1) at but initiation and 50% flowering stages increased grain yields considerably from 225 to 900 kg ha-1 for cowpea planted in July and August. Cost-benefit analysis indicated that the insecticide application was more profitable for cowpea planted in late July and August than was the case when planted in June and early July. This seems to suggest that early maturing elite cultivars could escape economic damage caused by post-flowering pests when cowpea is planted early in the season. The implication of these findings to the grower and the breeding strategy at IITA is discussed in this paper.